International journal of e-services & mobile applications (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2009)
The objective of the International Journal of E-Services and Mobile Applications (IJESMA) is to be a truly interdisciplinary journal providing comprehensive coverage and understanding of all aspects of e-services, self-services and mobile communication from different fields including marketing, management, and MIS. The journal invites contributions that are both empirical and conceptual, and is open to all types of research methodologies both from academia and industry.